STRATEGI KEUNGGULAN BERSAING DALAM PENGEMBANGAN PERGURUAN TINGGI ISLAM: (Studi Multikasus Universitas Islam Negeri Maulana Malik Ibrahim Malang dan Universitas Muhammadiyah Malang) - Duki (JURNAL PUSAKA, 2023)
This study aim to discusses the concepts, strategies, and implications of competitive advantage in Islamic tertiary institutions. Furthermore, the purpose of this study is to analyze and find about the concepts, strategies, and implications of competitive advantage in Islamic tertiary institutions. This study uses a qualitative method with a multi-case study type of research. The research locations were at the State Islamic University of Maulana Malik Ibrahim Malang and Muhammadiyah University of Malang, data collection techniques were in-depth interviews, observation, participation and documentation studies. Data analysis was carried out through three stages, namely data presentation, data condensation, and drawing conclusions in each case, followed by a comparative study of the two cases. As for checking the validity of the data researchers carried out with credibility, transferability, dependability, and confirmability. The results of this study are: First, the concept of competitive advantage in the development of Islamic tertiary institutions is to carry out general tips/patterns in plans and actions focused on the vision and mission to become an Islamic tertiary institution. Leading (superior) with special characteristics and religious character. The differentiation of UIN Malang is the integration of Islam with the character of Ulul Albab while UMM integrates science and technology with the character of progressing Islam, being Indonesian and modern. Second, strategic steps for competitive advantage in the development of Islamic tertiary institutions are determining uniqueness, conducting internal and external environmental analysis, making programs and policies, improving human resource capabilities, building reputation, improving infrastructure, improving services and having business units. Third, the implications of building strategy building competitive advantage in the development of Islamic tertiary institutions can be seen through the progress achieved, namely receiving appreciation and recognition from various groups, both national and international levels. Institutional, academic, HR, infrastructure, funding have increased.